An Update on Postoperative Cognitive Dysfunction Following Cardiac Surgery - Vu, Tony; Smith, Julian A. (Frontiers in Psychiatry, 2022)
Postoperative cognitive dysfunction is extremely prevalent following cardiac surgery. The increasing patient age and comorbidity profile increases their susceptibility to cognitive impairment. The underlying pathophysiological mechanisms leading to cognitive impairment are not clearly elucidated. Using the contemporary literature (2015 – present), this narrative review has three aims. Firstly, to provide an overview of postoperative cognitive impairment. Secondly, to analyze the predominant pathophysiological mechanisms leading to cognitive dysfunction following cardiac surgery such as inflammation, cerebral hypoperfusion, cerebral microemboli, glycaemic control and anaesthesia induced neurotoxicity. Lastly, to assess the current therapeutic strategies of interest to address these pathophysiological mechanisms, including the administration of dexamethasone, the prevention of prolonged cerebral desaturations and the monitoring of cerebral perfusion using near-infrared spectroscopy, surgical management strategies to reduce the neurological effects of microemboli, intraoperative glycaemic control strategies, the effect of volatile vs intravenous anaesthesia, and the efficacy of dexmedetomidine.